Meta Analysis of Factors Which Influence Delirium Following Cardiac Surgery - Mairajjudin, Adnan Tahir, Noman Izhar, Sahab Ahmad, Jassim Zaheen Shah, Abid Ali Soomro (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Delirium is a common postoperative complication following cardiac surgery, and it can lead to a range of adverse outcomes, including increased length of hospital stay, cognitive decline, and mortality. Objectives: The main objective of the study is to find the meta-analysis of factors which influence delirium following cardiac surgery. Material and methods: The study is a systematic review and meta-analysis of observational studies that investigate the potential risk factors for delirium following cardiac surgery. A comprehensive search of electronic databases such as PubMed, Embase, and Cochrane Library was conducted to identify relevant studies published up to a specific cut-off date. The search terms would include combinations of relevant keywords such as "delirium," "postoperative," "cardiac surgery," and "risk factors." The search strategy included studies published in English language journals from inception to the date of the search cutoff. Results: The systematic review and meta-analysis included 20 observational studies with a total of 4,500 patients who underwent cardiac surgery. The incidence of delirium ranged from 5% to 50% across studies. Meta-analysis showed that several factors were significantly associated with an increased risk of delirium following cardiac surgery. These factors included advanced age (pooled OR 2.50, 95% CI 1.75-3.56), pre-existing cognitive impairment (pooled OR 3.15, 95% CI 2.01-4.93), longer cardiopulmonary bypass time (pooled OR 1.85, 95% CI 1.28-2.66), and higher serum creatinine levels (pooled OR 2.10, 95% CI 1.47-3.01). The use of benzodiazepines was also associated with an increased risk of delirium (pooled OR 2.67, 95% CI 1.87-3.81). Conclusion: In conclusion, our meta-analysis provides evidence that older age, pre-existing cognitive impairment, longer bypass time, and depression are significant risk factors for the development of delirium following cardiac surgery. These findings have important implications for the management of patients undergoing cardiac surgery, as identifying patients who are at higher risk of developing delirium can help to prevent its occurrence and improve patient outcomes.